2012
DOI: 10.1002/rra.2591
|View full text |Cite
|
Sign up to set email alerts
|

Fish Assemblages in Non‐regulated and Regulated Rivers From Permanent and Temporary Iberian Systems

Abstract: The effects of river regulation on the hydrological cycle of a river and on the respective fish assemblage may differ according to dam operation purpose and type of river analysed. To assess the spatial and temporal variation of fish assemblages and their response to the hydrological changes caused by two different types of flow regulation, we selected three sampling sites in four rivers with different levels of regulation, two in a permanent river system and another two on a temporary one, which we sampled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…In contrast, the few studies that have explored variation in fish assemblages across seasons found no significant differences in diversity [86] or fish assemblage structure [90], despite considerable variation in environmental conditions among seasons. However, Alexandre et al [91] explored seasonal variation in fish assemblages from regulated and non-regulated rivers in a temporary and permanent Iberian system, and found higher variation in non-regulated than regulated systems, and higher seasonal variation in the temporary system examined compared to the permanent one. The changes in fish communities in the temporary systems, however, were mainly related to the presence of exotic species, which hinder natural community patterns from forming.…”
Section: Fish Communitiesmentioning
confidence: 99%
“…In contrast, the few studies that have explored variation in fish assemblages across seasons found no significant differences in diversity [86] or fish assemblage structure [90], despite considerable variation in environmental conditions among seasons. However, Alexandre et al [91] explored seasonal variation in fish assemblages from regulated and non-regulated rivers in a temporary and permanent Iberian system, and found higher variation in non-regulated than regulated systems, and higher seasonal variation in the temporary system examined compared to the permanent one. The changes in fish communities in the temporary systems, however, were mainly related to the presence of exotic species, which hinder natural community patterns from forming.…”
Section: Fish Communitiesmentioning
confidence: 99%
“…To act as “reference” in this study, we selected River Vez (nonregulated river [NRR]), a NRR located in River Lima basin, with 38 km of length and a drainage area of 264 km 2 . Despite being in distinct river basins, both studied rivers are similar in terms of abiotic and biotic (i.e., fish assemblage) typologies (Alexandre, Ferreira, & Almeida, ; INAG I. P., ; Matono et al, ), which allows to compare them, with a high level of confidence.…”
Section: Methodsmentioning
confidence: 99%
“…A more detailed characterization of the studied rivers and of the main streamflow (30‐year time series, 1974–2004, collected from the Portuguese Environmental Agency Database; SNIRH, ) and thermal (obtained with data loggers Water Temp Pro V2 from HOBO during the study period) regimes differences between them is presented by Alexandre et al (, ) and Alexandre, Sales, et al (). In short, only slight differences are observed between the two rivers regarding their seasonal temperature variation pattern, which occur mostly in the end of spring and summer when the NRR presents higher average daily temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenic disturbance in a system can further support nonindigenous generalist fish establishment through changes to the flow regimen, reduction of water availability, and nutrient loading. (Brisbois et al 2008;Dowling 2012;Kopp et al 2012;Leprieur et al 2008; Moyle and Light 1996;Phillips and Johnston 2004a) Flow depletion and reduced flow variability have been demonstrated to favor generalists over fluvial specialists in a number of studies in the Southeastern United States (Alexandre et al 2013;Clavero and Hermoso 2011;Kanno and Vokoun 2010) as well as the arid western United States (Propst et al 2008). Beyond providing favorable abiotic conditions to introduced species, anthropogenic disturbance can influence community level interactions between nonindigenous species and native competitors by giving the invaders a competitive advantage for prey and increased reproductive potential compared to native fishes (Dowling 2012;Johnston and Maceina 2009;Phillips and Johnston 2004b;Wagner and Grossman 2013).…”
Section: Introductionmentioning
confidence: 97%